Implementasi Kebijakan Pengawasan Metrologi Legal melalui Edukasi di Media Sosial Direktorat Metrologi - Putri, Ariana Nashya Sandi; Sudrajat, Achmad Sodik; Gedeona, Hendrikus Tribawanto; Mursalim, Siti Widharetno (Jurnal Studi Ilmu Sosial dan Politik, 2025)
Purpose: This study analyzes the implementation of the Legal Metrology supervision policy through educational content on Instagram by the Directorate of Metrology. The objective is to evaluate the effectiveness of this digital communication strategy and identify the key factors that influence policy implementation. Ensuring accurate measurements and protecting consumer rights are central to the policy’s intent. Methodology/Approach: A descriptive qualitative approach was adopted, utilizing Van Meter and Van Horn’s implementation theory as the primary analytical framework. In addition, a SWOT analysis was conducted to identify internal strengths and weaknesses, as well as external opportunities and threats, to formulate strategic recommendations for improvement. Results/Findings: The findings indicate that using Instagram for policy implementation is moderately effective but has not reached its full potential. Several obstacles were identified, including limited human resources, internal organizational constraints, and low levels of public engagement. Conclusions: The Directorate of Metrology has made notable progress in leveraging digital platforms for public education and outreach. Nonetheless, there is a need for targeted strategic improvements. Enhancing human resource capacity, improving content quality, and adopting more effective outreach strategies are essential to increasing overall effectiveness and building greater public trust in legal metrology practices. Limitations: This study is limited to qualitative analysis and does not include quantitative measurements of social media engagement or comparisons with other governmental institutions. Contribution: The study offers practical insights into optimizing social media for policy implementation, supervision, and consumer protection.